THE STUDY ON THE INFLUENCE OF ZEPTO’S PROMOTIONAL APPROACH ON SOCIAL MEDIA PLATFORMS. - MS. ANUSMITA PAUL, Asst. Prof. SANTOSH.S (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This study explores the significant impact of Zepto’s advertising techniques as it is promoted on social media platforms. This study aims to determine the effectiveness and relevance of Zepto’s marketing strategies in the era of the digital world for which brand visibility and engagement are very competitive. By examining the interplay between social media dynamics, it uncovers the strategies through which it promotes, creates a perception and brand image among consumers, and makes a stand in the overall market. The study has unfolded all the important and complex strategies that offer insights into modern marketing techniques. This study has investigated Zepto's promotional approach on social media platforms. The study uses a quantitative approach to the age group of 18-25 years. It is being conducted in Bangalore’s demographic area. Beyond basic visibility, this research aims to look into how Zepto's marketing strategies can connect with its viewers and consumers, which influences them to have an interactive connection in the emerging world of digitalization.